Marketing Strategy Analysis of Betta Ornamental Fish Farming Business Perspectives on Islamic Business Ethics (Case Study di Desa Bendiljati Sumbergempol Tulungagung) - M. Abdul Khafid Zainur Rokhim; Muhammad Alhada Fuadilah Habib (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
A well-designed, prepared, and evaluated marketing strategy is the basis for determining the success rate of a business. The purpose of this study is to describe the Marketing Strategy Analysis of Betta Ornamental Fish Farming Business Perspective of Islamic Business Ethics in Bendiljati Sumbergempol Tulungagung Village. Researchers use descriptive qualitative research methods to describe the marketing strategies applied. Data collection techniques in this study include; interviews, observations, and documentation. Data analysis techniques use data source triangulation tests with the stages of data reduction, data presentation, and conclusion drawing. The results of the study stated that Bendiljati Village succeeded in increasing sales of betta ornamental fish with a 7P marketing mix strategy; product, price, place, promotion, people, physical evidence, and process, which are combined with the principles of Islamic business ethics. The products sold are betta ornamental fish with attractive prices and purchase bonuses, clean, comfortable, and easily accessible cultivation places, using offline and online promotion strategies through social media, providing training program facilities for fish farmers in order to maintain and improve the quality of the fish produced, a good cultivation process so that they can produce good fish quality, Beautiful shape, various shades of color and size, so that it can attract consumers and make sales continue to increase every year. There are six principles of Islamic business ethics applied; honest in quantity, selling good quality goods, not using oaths, being loose and generous in serving buyers, building good relations between colleagues by maintaining friendship between sellers and buyers, and setting prices transparently; conveys the price according to the actual state of the fish.